Dryland farming in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The agricultural development of dryland Africa presents formidable problems. It should not be supposed that drought is always the only, or even the major, constraint to crop production in dry regions. Social, economic, political and ecological...